Who returns to work and why? Six country study on work incapacity and reintegration - Bloch, Frank S.; Prins, Rienk (New Brunswick, 2000)
"Discusses findings from the Work Incapacity and Reintegration (WIR) Project, a cross-national study of work incapacity and return to work which focused on low back pain patients."